Effect of addition of organic inhibitor of kersen leaf extract (Muntingia calabura L) on corrosion rate on A36 steel in seawater media - Syamsul Hidayat; Rita Desiasni; Nita Novia (Jurnal Pijar Mipa, 2023)
Organic inhibitors utilization to reduce corrosion rate on metal has been widely studied because of their environmentally friendly nature. This study aims to calculate the value of the corrosion rate of A36 steel, the efficiency of inhibitors from the extract of Kersen leaf, and determine the corrosion that occurs in the material of A36 steel. The method used is weight loss. The sample was immersed for seven days with inhibitor concentration variations of 0 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm. The results showed that the extract of Kersen leaf can reduce the corrosion rate. The corrosion rate decreases as the number concentration of the inhibitor is added to the test medium. In contrast, the inhibitor efficiency increases with increasing amounts of inhibitor concentrations added to the test medium. The lowest corrosion rate value and the highest efficiency at adding 500 ppm inhibitor concentration are 0,0767 mmpy and 38,83%, respectively. Based on the results of the microstructure of A36 steel after immersion, pitting corrosion is formed in the form of holes on the steel surface. On steel without inhibitors, corrosion products are more, and the surface is rougher than steel samples added with inhibitors.